2018
DOI: 10.18632/oncotarget.25540
|View full text |Cite
|
Sign up to set email alerts
|

Oral inflammation promotes oral squamous cell carcinoma invasion

Abstract: Oral squamous cell carcinoma (OSCC) represents 95% of oral malignancies and invasion, and metastasis underlies disease morbidity and mortality. We recently established a direct link between oral inflammation and cancer invasion by showing that neutrophils increase OSCC invasion through a tumor necrosis factor (TNFα)-dependent mechanism. The objective of this study was to characterize OSCC-associated inflammation and to determine the molecular mechanisms underlying inflammation-mediated OSCC invasion. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 49 publications
(58 reference statements)
6
77
0
Order By: Relevance
“…The increase in TNF-α concentration correlated with higher T and N parameters was also confirmed by our study. Excessive TNF-α concentration in the tumor microenvironment shifts the balance towards invasion, resulting in a reduction in overall survival and disease-free survival [26]. Our study also showed an increase in TNF-α concentration in the saliva of patients with positive aerobic bacterial culture of oral swabs.…”
Section: Discussionsupporting
confidence: 65%
“…The increase in TNF-α concentration correlated with higher T and N parameters was also confirmed by our study. Excessive TNF-α concentration in the tumor microenvironment shifts the balance towards invasion, resulting in a reduction in overall survival and disease-free survival [26]. Our study also showed an increase in TNF-α concentration in the saliva of patients with positive aerobic bacterial culture of oral swabs.…”
Section: Discussionsupporting
confidence: 65%
“…Cytokines and cytokine-coding mRNA in saliva are also shown to be predictors for OSCC progression ( 51 ). Goertzen et al showed that cancer patients have significantly increased pro-inflammatory cytokines, such as IL-1α, IL-1β, IL-6, IL-8 and TNF-α in saliva, as compared to controls ( 122 ). Salivary levels of IL-6 ( 118 , 119 ) may serve as oral cancer predictors ( 123 ).…”
Section: Changes In Oral Cavity Microenvironment Due To Oral Cancermentioning
confidence: 99%
“…Oral cancers are malignant lesions occurring within the oral cavity, and more than 90% of oral cancer cases are oral squamous cell carcinoma (OSCC) . The symptoms of early OSCC, precancer, and non‐cancer lesions cannot be differentiated visually and requires histopathological investigation for the diagnosis of lesions.…”
Section: Introductionmentioning
confidence: 99%
“…7 Oral cancers are malignant lesions occurring within the oral cavity, and more than 90% of oral cancer cases are oral squamous cell carcinoma (OSCC). 8 The symptoms of early OSCC, precancer, and non-cancer lesions cannot be differentiated visually and requires histopathological investigation for the diagnosis of lesions. HPV16 has been commonly reported in cases with HPV-positive head and neck cancer [9][10][11] and is frequently associated with oral cancer lesions in north Indian populations.…”
mentioning
confidence: 99%